Mutant-IDH1-dependent chromatin state reprogramming, reversibility, and persistence. (January 2018) - Turcan, Sevin; Makarov, Vladimir; Taranda, Julian; Wang, Yuxiang; Fabius, Armida; Wu, Wei; Zheng, Yupeng; El-Amine, Nour; Haddock, Sara; Nanjangud, Gouri; LeKaye, H.; Brennan, Cameron; et al.
Abstract Mutations inIDH1 andIDH2 (encoding isocitrate dehydrogenase 1 and 2) drive the development of gliomas and other human malignancies. Mutant IDH1 induces epigenetic changes that promote tumorigenesis, but the scale and reversibility of these changes are unknown. Here, using human astrocyte and glioma tumorsphere systems, we generate a large-scale atlas of mutant-IDH1-induced epigenomic reprogramming. We characterize the reversibility of the alterations in DNA methylation, the histone landscape, and transcriptional reprogramming that occur followingIDH1 mutation. We discover genome-wide coordinate changes in the localization and intensity of multiple histone marks and chromatin states. Mutant IDH1 establishes a CD24+ population with a proliferative advantage and stem-like transcriptional features. Strikingly, prolonged exposure to mutant IDH1 results in irreversible genomic and epigenetic alterations. Together, these observations provide unprecedented high-resolution molecular portraits of mutant-IDH1-dependent epigenomic reprogramming. These findings have substantial implications for understanding of mutant IDH function and for optimizing therapeutic approaches to targeting IDH-mutant tumors. This study uses human astrocytes and glioma tumorspheres to generate an atlas of mutant-IDH1-induced epigenomic reprogramming. The findings have implications for understanding mutant IDH function and for optimizing approaches to target IDH-mutant tumors.